Globalized religion and sexual identity : contexts, contestations, voices - Shipley, Heather. (International Studies in Religion and Society, 2014)
Globalized Religion and Sexual Identity reflects on the ways religion, gender and sexual identity are framed and regulated in multiple spheres across the globe. Controversies in the public arena regarding religion and sexual identity often construct these categories as inherently oppositional or already in conflict. As state policies regarding sexuality and sexual diversity develop, promoting inclusivity and non-discrimination, it is imperative to develop a more nuanced discussion regarding the relationship of religion/ideology to sexual diversity and sexuality. The goal of this volume is to explore religion and sexual identity from a range of countries across the globe, focusing on the theme of religious/ideological voices in state policies, such as same-sex marriage, identification, and education.